The effectiveness of gotu kola leaf extract gel (centella asiatica (l.) urban) as an antimicrobial against staphylococcus aureus bacteria in vitro - Ahyar Riza; Nurul Rizki (Journal of Dentomaxillofacial Science, 2021)
Objective: To determine the effectiveness of gotu kola leaf extract gel (Centella asiatica (L.) Urban) as an antimicrobial against the growth of Staphylococcus aureus bacteria in vitro and the most effective concentration in inhibiting the growth of Staphylococcus aureus bacteria.Materials and Methods: This study is a laboratory experimental study with a post-test only control group design. The research sample used Staphylococcus aureus bacteria which was bred and cultured in the Microbiology Laboratory of the Universitas Sumatera Utara Hospital. The research sample was divided into 5 treatment groups, namely gotu kola leaf extract gel 1%, 2.5%, 5%, Chlorhexidine digluconate 0.2% (positive control) and DMSO (negative control). The test for the five groups was repeated 5 times with the Kirby-bauer diffusion method.Results: The results showed the effectiveness of gotu kola leaf extract gel at a concentration of 2.5% and 5% with an inhibition zone diameter of 6.8 mm and 9.4 mm, respectively, while at a concentration of 1% there was no inhibition zone found. The data were statistically analyzed using the Kruskal-wallis and Mann-Whitney tests showing a significant difference in each treatment group (p <0.05), but there was no significant difference between the 1% and negative control groups (p> 0.05).Conclusion: Gotu kola leaf extract gel was effective in inhibiting the growth of Staphylococcus aureus bacteria in vitro at concentrations of 2.5% and 5%. The 5% concentration is more effective than other concentrations.